Diseño de un sistema de costos para la empresa m&m Plasticotopaxi ubicada en la ciudad de Latacunga, durante el segundo trimestre del año 2022 - Chiluisa Caillagua, Johanna Lizbeth (2023)
This integrating project focused on analyzing the M&M Plasticotopaxi Company, the same one that is dedicated to the production of plastic covers, which until now does not have an appropriate cost system, its prices have been established empirically causing problems in its profitability. , a system of costs for production orders is designed for the company allowing to determine the real total of each one and to obtain in an adequate way their real values.